2016
DOI: 10.1086/688667
|View full text |Cite
|
Sign up to set email alerts
|

High-quality algae attached to leaf litter boost invertebrate shredder growth

Abstract: Algae are higher-quality food resources than allochthonous plant litter for stream invertebrates, in part, because of their higher content of polyunsaturated fatty acids (PUFAs). We tested the hypothesis that algal biofilms on the surfaces of leaf litter improve the nutritional quality of terrestrial inputs for invertebrate shredders. We used a laboratory feeding experiment with 2 light levels (open and shaded) and 2 nutrient regimes (ambient and enriched) to manipulate the algal biofilms that form on leaf sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 49 publications
6
81
0
Order By: Relevance
“…Differences in the FA composition among aquatic macroinvertebrates, periphyton, and terrestrial leaves suggest that periphyton is the main LC‐PUFA (in particular EPA) source for macroinvertebrates. Although submerged leaves were not available in our study streams in summer and FA of biofilms attached to submerged leaves were not analyzed, previous studies report that submerged leaves as a whole contained no or very little EPA, < 1% (Brett et al ; Torres‐Ruiz and Wehr ; Guo et al c ), which is also confirmed by our leaf FA (Table ). Moreover, seasonal change is unlikely to affect the low‐EPA content of submerged leaves (Torres‐Ruiz and Wehr ).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Differences in the FA composition among aquatic macroinvertebrates, periphyton, and terrestrial leaves suggest that periphyton is the main LC‐PUFA (in particular EPA) source for macroinvertebrates. Although submerged leaves were not available in our study streams in summer and FA of biofilms attached to submerged leaves were not analyzed, previous studies report that submerged leaves as a whole contained no or very little EPA, < 1% (Brett et al ; Torres‐Ruiz and Wehr ; Guo et al c ), which is also confirmed by our leaf FA (Table ). Moreover, seasonal change is unlikely to affect the low‐EPA content of submerged leaves (Torres‐Ruiz and Wehr ).…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, although periphyton FA showed a limited effect on shredder FA, shredder EPA was still 6.9 times higher than in periphyton, suggesting shredders assimilate EPA very efficiently. It is well studied that shredders prefer feeding on conditioned rather than fresh leaves (Nolen and Pearson ; Pearson and Connolly ; Allan and Castillo ), and biofilms attached to leaf surfaces are a potential source of EPA (Torres‐Ruiz and Wehr ; Guo et al c ). However, in summer, conditioned leaves were not available in our streams, and it has been frequently reported in previous studies that shredders may face seasonal shortages of conditioned leaves during the late spring and summer period (Dobson and Hildrew ; Wallace et al ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations match with the prediction that even highly covered tropical streams have enough light incidence to sustain a reasonable level of primary produc- (Bunn et al, 1999a(Bunn et al, , 1999bLau et al, 2009). In this manner, we speculate that shredders may be consuming some autochthonous carbon along with their predominant diet of leaves and that they might benefit from algae attached to leaves (Guo et al, 2016).…”
Section: Shredders Accumulated Leaves and Breakdown Ratessupporting
confidence: 88%